2013
DOI: 10.1039/c3dt50288k
|View full text |Cite
|
Sign up to set email alerts
|

A novel single-site manganese(ii) complex of a pyridine derivative as a catalase mimetic for disproportionation of H2O2 in water

Abstract: A novel single site Mn(II) complex was successfully synthesized and tested in the aqueous disproportionation of hydrogen peroxide. The complex was found to be stable (HR-XAS) and exhibits catalase-like activity in neutral pH. Theoretical calculations suggested a reaction mechanism involving two complexes, changes in metal oxidation state and proton shuttling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…It can be seen that, independently from the solvent, the present complex reacts at similar rate as mononuclear Mn complexes with one or two labile coordination positions on the Mn ion [7][8][9][10][11][12][13][14][15][17][18][19]. Catalysts evaluated in aqueous media require the addition of exogenous base to show activity.…”
Section: •−mentioning
confidence: 92%
See 1 more Smart Citation
“…It can be seen that, independently from the solvent, the present complex reacts at similar rate as mononuclear Mn complexes with one or two labile coordination positions on the Mn ion [7][8][9][10][11][12][13][14][15][17][18][19]. Catalysts evaluated in aqueous media require the addition of exogenous base to show activity.…”
Section: •−mentioning
confidence: 92%
“…The intrinsic dinuclear nature of the MnCAT active site has stimulated activity studies on complexes of binucleating ligands which provide an internal bridge to stabilize the dimanganese unit [6,16]. However, a number of mononuclear Mn complexes have shown CAT activity, for which efficiency seems to be related to the presence of at least one labile coordination position on the Mn ion [7][8][9][10][11][12][13][14][15][17][18][19]. This kind of mononuclear catalytic antioxidants has been proposed to react through a mechanism involving mononuclear Mn V = O species [20,21] or through formation of dimeric species in solution [22].…”
Section: Introductionmentioning
confidence: 98%
“…Studies have shown the ability of hydrazone based complexes of manganese as potential biomimics for manganese enzymes [1,3,4]. The present work constitutes the exploration of the coordination chemistry of manganese with ligand bis(2-hydroxy-1-naphthaldehyde)adipoyldihydrazone (npahH 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the metal complex stability increases with the topological complexity of the ligand recognized in the chelate effect, the macrocyclic effect, and the cryptate effect. Now, we want to retain the features of this tetraligand npahH 4 and explore the level of stability when a second monodentate or bidentate ligand coordinates to the metal center and compare the changes achieved in the topologically constrained environment of the metal complex. N-donor ligands being particularly active as functional biomimics for manganese enzymes [3,4], pyridine and its methyl derivatives were preferably selected as secondary ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation